Broadcasting Regulation Shift From Authoritarian Control To Digital Disparity: Pergeseran Regulasi Penyiaran dari Pengawasan Otoriter ke Ketimpangan Digital - Yinta Syifaudiana Yulianti; M Tanzil Multazam (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Broadcasting systems function as central institutions for disseminating information, shaping public discourse, and reflecting societal values within political and technological contexts. Specific Background: Indonesia’s broadcasting landscape has undergone major regulatory transformation from the New Order’s centralized control to the Reform era’s democratization, decentralization, and expansion of private and local media institutions. Knowledge Gap: Despite these transitions, existing legal frameworks have not kept pace with rapid digitalization, particularly regarding internet-based distribution and over-the-top platforms, resulting in unequal governance between conventional broadcasters and digital services. Aims: This study analyzes the evolution of broadcasting regulations from the New Order to the Reform period and examines their alignment with technological developments. Results: Findings indicate that the New Order employed strict state control to manage ideology and public opinion, whereas the Reform era introduced press freedom, the Network Station System, and Local Public Broadcasting Institutions, although implementation encountered obstacles such as media conglomerate dominance and regional infrastructure disparities. The rise of internet-based media shifted audiences toward digital platforms, while regulatory adaptation remained limited, producing gaps in oversight and accountability. Novelty: The study offers a comprehensive legal trajectory linking political transition, decentralization policy, and digital disruption within Indonesia’s broadcasting governance. Implications: The findings highlight the urgency of revising regulatory frameworks to ensure equitable supervision, legal certainty, and democratic media development in the digital environment. Highlights: State monopoly during the earlier political period restricted content diversity and public access to alternative viewpoints. Post-1998 policy reforms introduced network-based structures and locally oriented public institutions but faced structural barriers. Rapid migration of audiences to internet services created governance gaps between legacy broadcasters and online providers. Keywords:Broadcasting Regulation; Digital Broadcasting; Media Decentralization; Over-The-Top Platforms; Indonesia